Analysis of Influencing Factors on Consumers' Willingness to Purchase Anhua Dark Tea Based on Perceived Value Model - Zuo, Shihua (Pacific International Journal, 2023)
Anhua dark tea, a rapidly growing industry since 2006, has played a pivotal role in poverty alleviation and economic prosperity for Anhua County. However, recent years have witnessed a decline in sales volume, raising concerns among scholars due to changing shopping environments, business models, and consumer demographics. Drawing upon consumer behavior theory and the perceived value model, this study proposes hypotheses to explore the factors influencing consumers' purchase decisions regarding dark tea, focusing on perceived functional value, social value, income value, and cultural value. By collecting Likert-scale data and basic information, the study employs SPSS and Amos for data analysis, aiming to validate the proposed hypotheses. The results indicate that perceived functional value, social value, and cultural value have a significantly positive impact on consumers' intention to purchase Anhua dark tea. Building on the empirical findings, this study suggests strategies such as standardized production, product structure adjustments, diversified product offerings, and the promotion of value-added and culturally enriched dark tea products. Furthermore, the study emphasizes the importance of establishing a comprehensive black tea industry chain, integrating tea culture with local communities, and enhancing product value and reputation through the creation of "product IP," "geographical IP," and "cultural IP" for Anhua dark tea. By fostering consumer loyalty, Anhua dark tea can emerge as a representative of Hunan Province and a symbol of Chinese tea culture, carrying its therapeutic potential to a global audience.